Improvement Web Dashboard Aplikasi Super dengan Menggunakan Metode Waterfall - Yohanes Ricky Wijaya (Jurnal Titra, 2022)
PT. Krakatau Karya Abadi, commonly known as the Super Application Startup, is a network of agents distributing necessities in small towns and remote areas. One of the divisions in Super Applications is the Product Manager division. The division is responsible for product planning and development. Products in the Product Manager division talk about applications and dashboard platforms used by management and super application users. The Product Manager Division will be directly responsible to the user for any development. When the product is released, a Product Manager will perform maintenance on the development and will fix if bugs or problems are found in the future.During the internship, the researcher completed several developments on the super application. In development, the method used is the waterfall method, where the work is carried out coherently from beginning to end.